Aplikasi Sistem Informasi Pertanahan Berbasis Website Pada Kantor Pertanahan Kabupaten Kupang Provinsi NTT - Indah Beatry Feysilya Lusi; Justinus Andjarwirawan; Yulia Yulia (Jurnal Infra, 2017)
Inproviding the information regarding managing the land certificate, Kantor Pertanahan Nasional of Kupang Regency was used manual system in which the applicants must come to the office directly. This kind of system caused difficulties for the society in obtaining some information about the land, the enrolment application, the certificate making status as wel as its completion.Feature contained in this application is the applicant can register the application for making land certificate. After that the counter clerk can view the application data and update the status of the certificate until the certificate is completed.The results of this application development are, the users are able to fill out the registration form, receive the land certificate progress information through website and receive SMS from each certificate service process. Furthermore, the application is also able to show the service information offered by the office, also, the officer can see the reports and graphs of certiciate making.